KEPEMIMPINAN ADAPTIF DALAM MENGHADAPI KRISIS: Studi Kasus pada PT Pertamina - Azahra Sabila; Prasti Registia Ningsih; Furkan; H. Abdurahman; Joswadi; Fantriansyah; M. Tazwin (STKIP Subang, 2026)
A crisis is a challenge that can disrupt the stability and effectiveness of public organizations in carrying out their functions of serving society. In situations characterized by uncertainty, public organizations require leadership that is capable of adapting to environmental changes, making responsive decisions, and maintaining public trust. This study aims to analyze the role of adaptive leadership in managing crises within public organizations and to identify the factors that support its effective implementation. This research employs a qualitative approach using the library research method. The data used are secondary data obtained from scientific journals, books, research reports, and academic documents relevant to the topics of adaptive leadership, crisis management, and public organizations. Data collection was conducted through documentation techniques and literature review from various scholarly sources. The data were then analyzed using content analysis through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that adaptive leadership plays a significant role in enhancing the ability of public organizations to respond to crises through three main aspects: responsive decision-making, effective communication, and the development of organizational resilience. Adaptive leaders are capable of adjusting strategies to evolving conditions, fostering transparent communication, and encouraging organizational learning to improve preparedness for future challenges. This study concludes that adaptive leadership is a strategic factor in strengthening the resilience of public organizations and ensuring the continuity of public services during times of crisis. Therefore, public organizations need to strengthen their adaptive leadership capacity through competency development, a learning-oriented culture, and effective communication systems.